The Effect Of Internal Audit And The Effectiveness Of Internal Control On The Ability To Detect Fraud - Yuliana, Khrisna Anggun; Badren, Yuliana (Amkop Management Accounting Review (AMAR), 2024)
Responding to fraud cases that arise in the field of higher education, it is crucial to take action to prevent fraud through the implementation of risk management in the implementation of the institution's business processes, with reference to Government Regulation No. 60 of 2008 and Education and Culture Regulation No. 66 of 2015. Based on the survey results presented in the 2019 Report to the Nations, the Association of Certified Fraud Examiners (ACFE), an international organization, shows attention to fraud prevention in various sectors. The survey results show that in terms of education, the majority of fraud perpetrators are Bachelor-level college graduates with a percentage of 73.2% (Association of Certified Fraud Examiners Indonesia, 2019). Furthermore, there are graduates with a Master's level reaching 17.2%, followed by diploma graduates 4.6%, then high school graduates 4.2%, and finally doctoral students 0.8%. The research data was collected through distributing questionnaires to targeted respondents, namely internal auditors in the internal control system section in LLDIKTI IV area universities. The questionnaires in this study were distributed with a total of 80 samples from 253 available questionnaires. The results of the study using multiple linear regression models show that internal auditors have no significant effect that can be proven through this study, and the effectiveness of internal control also does not show a significant effect in the researcher.